Open Profiling of Quality: A Mixed Method Approach to Understanding Multimodal Quality Perception. (25th July 2010) - Strohmeier, D.; Jumisko-Pyykkö, S.; Kunze, K.
Abstract : To quantify the excellence of multimedia quality, subjective evaluation experiments are conducted. In these experiments, the tradition of quantitative assessment is the most dominating, but it disregards the understanding of participants' interpretations, descriptions, and the evaluation criteria of quality. The goal of this paper is to present a new multimedia quality evaluation method called Open Profiling of Quality (OPQ) as a tool for building a deeper understanding on subjective quality. OPQ is a mixed method combining a conventional quantitative psychoperceptual evaluation and qualitative descriptive quality evaluation based on the individual's own vocabulary. OPQ is targeted for naïve participants applicable to experiments with heterogeneous and multimodal stimulus material. The paper presents the theoretical basis of the development of OPQ and overviews the methods for audiovisual quality research. We present three extensive quality evaluation studies where OPQ has been used with 120 participants. Finally, we conclude further recommendations of use of the method in quality evaluation research.